Demethylating agents in combination with CD7-targeted CAR-T for the successful treatment of a case with mixed-phenotype acute leukemia relapsed after allogeneic hematopoietic stem cell transplantation: A Case Report - Han, Ying; Yao, Hao; He, Guang-cui; Lai, Si-han; Deng, Yan; Zhang, Shan; He, Ying; Xiong, Yi-song; Chang, Alex H.; Su, Yi; Yi, Hai (Frontiers in Immunology, 2023)
Background: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) has cured many patients with malignant hematologic diseases such as mixed phenotype acute leukemia (MPAL), while those relapsing after allo-HSCT still exhibit high mortality, poor prognosis, and no standard treatment modalities. It is necessary to explore more therapeutic modalities for patients with post-transplant relapse to obtain a better prognosis.Case Presentation: In this case report, a young male with MPAL received allo-HSCT after reaching complete remission (CR) by induction chemotherapy. Unfortunately, relapse of both myeloid and T lineages occurred nine months later. After receiving demethylating chemotherapy, myeloid lineage measurable residual disease (MRD) turned negative. T-lineage MRD turned negative after CD7-targeted chimeric antigen receptor (CAR)-T cell therapy. The bone marrow remained MRD-negative for 4 months. This case preliminarily demonstrated a long-lasting CR with CD7-targeted CAR-T cell therapy, allowing a better prognosis.Demethylating drugs combined with CD7-targeted CAR-T cell therapy is feasible in treating MPAL patients with relapse after transplantation, with good efficacy and safety, which will be a promising treatment option for MPAL.